2018
DOI: 10.1109/jphot.2018.2874270
|View full text |Cite
|
Sign up to set email alerts
|

Free-Space to Fiber Coupling of Electromagnetic Gaussian Schell-Model Beams in Turbulent Marine Atmospheric Channel

Abstract: We present a method to analyze the fiber coupling efficiency η of electromagnetic Gaussian Schell-model (EGSM) beams propagating through marine atmospheric turbulence. The expression for η is derived from the relation of field distributions between EGSM beam and fiber mode. The influence factors of η are discussed, including the properties of EGSM beam, focusing lens, and turbulence. We find that η declines as the turbulence enhances. A large-aperture lens and an EGSM beam with high coherence, long wavelength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Thus, it is important and necessary to investigate the propagation properties of array beam under the atmospheric and oceanic turbulence. Up to now, many works have been carried out on the propagation properties of laser array beams propagating through atmospheric and oceanic turbulence [13]- [26]. Besides, it has been found that laser beams with low coherence can suffer from smaller intensity fluctuations under influence of atmospheric turbulence [27], [28], which can improve the performance of communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important and necessary to investigate the propagation properties of array beam under the atmospheric and oceanic turbulence. Up to now, many works have been carried out on the propagation properties of laser array beams propagating through atmospheric and oceanic turbulence [13]- [26]. Besides, it has been found that laser beams with low coherence can suffer from smaller intensity fluctuations under influence of atmospheric turbulence [27], [28], which can improve the performance of communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…The basic model for coupling was established and the coupling efficiencies of different beams were analyzed, such as plane wave and Gaussian beam [2]- [4]. The coherence and polarization of beam source were also considered in coupling [5]. Given that atmospheric turbulence causes the distortion of free-space beams, its effects on coupling and mitigation ways attract attention.…”
Section: Introductionmentioning
confidence: 99%